1973
DOI: 10.1002/j.1551-8833.1973.tb01903.x
|View full text |Cite
|
Sign up to set email alerts
|

Virus Removal in Hawaiian Soils

Abstract: This article reveals the surprising degree to which some types of soil remove viruses before they reach water‐supply sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1974
1974
1979
1979

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Previous studies have indicated that human enteric viruses can survive for extended periods in some soil environments (8,11). Most investigators have reported only slight movement of viruses through soils during percolation of various liquids (4,6,16,21). Recent reports by Wellings et al (20) and Schaub et al (17) suggest, however, that in some soil systems enteric viruses can be recovered at considerable distances from their source.…”
mentioning
confidence: 99%
“…Previous studies have indicated that human enteric viruses can survive for extended periods in some soil environments (8,11). Most investigators have reported only slight movement of viruses through soils during percolation of various liquids (4,6,16,21). Recent reports by Wellings et al (20) and Schaub et al (17) suggest, however, that in some soil systems enteric viruses can be recovered at considerable distances from their source.…”
mentioning
confidence: 99%
“…Virus removal by soil is believed largely due to adsorption, in contrast to bacteria which are removed by a combination of filtration, sedimentation, and adsorption (4,11). Few studies which have been done on viral adsorption to soil have used poliovirus and/or certain bacteriophages as the indicator viruses for predicting the adsorptive behavior of all enteric viruses (2,4,5,11,16,18,30). It has been found, however, that coliphages do not necessarily behave in the same manner as poliovirus in their adsorption to soils (30).…”
mentioning
confidence: 99%
“…Few studies which have been done on viral adsorption to soil have used poliovirus and/or certain bacteriophages as the indicator viruses for predicting the adsorptive behavior of all enteric viruses (2,4,5,11,16,18,30). It has been found, however, that coliphages do not necessarily behave in the same manner as poliovirus in their adsorption to soils (30). The present study was undertaken to compare the adsorption of a number of different types and strains of human enteroviruses, a simian rotavirus, and bacteriophages to different types of soils.…”
mentioning
confidence: 99%
“…Since viruses are coated by proteins which are amphoteric, their adsorption in the soil is pH dependent, 35 with adsorption being more rapid at low than at high pH. 3 6 Adsorption of viruses in soil is also affected by the concentration and type of cations in the wastewater or soil solution.…”
Section: Quality Improvementmentioning
confidence: 99%